2020
DOI: 10.3126/njn.v17i3.33122
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinicoradiological Profile and Outcome of Traumatic Basal Ganglia Hematoma: A Perspective from Level 1 Trauma Center

Abstract: Introduction: This study was conducted to analyze clinico-radiological profile of traumatic basal ganglia hematoma and identify its prognostic factors. Methods and Materials: A prospective study was conducted in the Department of neurosurgery, Trauma center of Banaras Hindu University from September 2016 to March 2020. All patients with traumatic basal ganglia hematoma based on admission CT scan were enrolled and their demographic, clinical, radiological details were maintained till the time of discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Several prognostic factors are thought to be associated with a poor outcome and include: advanced age; post-resuscitation GCS <7; abnormal pupillary response; abnormal response to pain; ventilator dependence; large hematoma volume (>20 ml); diffuse axonal injury (DAI); association with parenchymal injuries; intraventricular haemorrhage or brain stem haemorrhage; association with coagulation disorder. 9 , 11 , 17 In the case reported here, despite the large size of the basal hematoma, the patient showed good recovery one month after hospital discharge and, two months later, had resumed normal life. Her mild cognitive deficits were probably associated with the DAI.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Several prognostic factors are thought to be associated with a poor outcome and include: advanced age; post-resuscitation GCS <7; abnormal pupillary response; abnormal response to pain; ventilator dependence; large hematoma volume (>20 ml); diffuse axonal injury (DAI); association with parenchymal injuries; intraventricular haemorrhage or brain stem haemorrhage; association with coagulation disorder. 9 , 11 , 17 In the case reported here, despite the large size of the basal hematoma, the patient showed good recovery one month after hospital discharge and, two months later, had resumed normal life. Her mild cognitive deficits were probably associated with the DAI.…”
Section: Discussionmentioning
confidence: 53%
“… 14 In one study of 41 patients with TBGH, 38% had a favourable prognosis and the mortality rate was 10%. 11 By contrast, other studies in smaller numbers of patients have found favourable outcomes in all patients with no mortality. 5 , 7 , 13 …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations